Growth and Production of Lemon Basil (Ocimum basilicum L.) Accessions Grown in Different Compositions of KCl Fertilizer and Cow Urine - Wawan Setiawan; Octavianus Lumban Tobing; Arifah Rahayu (Universitas Djuanda Bogor, 2018)
Lemon basil (Ocimum basilicum L.) is an indigenous plant which is commonly used as vegetable,medicinal herb, cosmetic ingredient, perfume ingredient, and food ingredient. This study was aimedat assessing the effects of the application of different compositions of KCl fertilizer and cattle urineon the growth and production of lemon basil accession. A factorial completely randomized designwith two factors was used. The first factor was the composition of KCl fertilizer and cattle urineconsisting of six levels, namely 100% R cattle urine 75% R cattle urine + 25% R KCl, 50% Rcattle urine + 50% R KCl, 25% R cattle urine + 75% R KCl, 100% R KCl, and 0% R cattle urine+ 0% R KCl. The second factor was lemon basil accession consisting of three levels, namely Bogor,Cianjur, and Sukabumi. Results showed that the composition of 25% R cattle urine + 75% R KCland 100% R cattle urine gave leaf area and total yield dry weight, respectively, which were higherthan those in other treatments. Bogor accession was found to have plant height, number of leaves,and length of branches which were significantly higher than those found in other accessions.Meanwhile, number of branches, leaf area, stem diameter, yield wet weight, and yield dry weightof Sukabumi accession were higher than those in Bogor and Cianjur accessions.Key words: Ocimum basilicum, leaf area, dry weight